Multilateral diplomacy and the NPT : an insider's account - Dhanapala, Jayantha; Rydell, Randy; United Nations Institute for Disarmament Research; International Institute for Peace and Conflict Research (Geneva, Switzerland : UNIDIR, 2005)
Concerns the Nuclear Non-Proliferation Treaty Review and Extension Conference (NPTREC) of 1995.
1. Introduction: an overview of the process leading to the indefinite extension -- 2. The 1995 conference preparatory process -- 3. Group positions at the conference -- 4. The adoption of the package -- 5. The review of the treaty in the committees -- 6. The aftermath -- 7. The NPT as a treaty regime -- 8. The road ahead -- Appendix A. Treaty on the non-proliferation on nuclear weapons ; B. "The package"--key documents of the NPTREC ; C. NPTREC closing statement by president Jayantha Dhanapala, 12 May 1995 ; D. Web-accessible statements by Jayantha Dhanapala on the NPT ; E. Research institutes and non-governmental organizations participating at the 1995 NPT review and extension conference.
"Foreword by United Nations Secretary-General Kofi A. Annan"--Cover
"SIPRI"--Cover
"UNIDIR/2005/3"--Title page verso
"United Nations publication. Sales no. GV. E.05.0.5"--Title page verso
Includes bibliographical references (pages 142-155).
Electronic reproduction.
Keywords: Traité sur la non-prolifération des armes nucléaires -- (1968 juin 12); Treaty on the Non-Proliferation of Nuclear Weapons (1968); Nuclear nonproliferation -- Congresses; Diplomacy; Nuclear disarmament -- Congresses; Non-prolifération nucléaire -- Congrès.; Désarmement nucléaire -- Congrès.; Diplomatie; diplomacy; LAW -- International; Nuclear disarmament; Diplomacy; Nuclear nonproliferation; Non-proliferatie.; Diplomatieke betrekkingen; Verdragenrecht; Diplomacia; Não-proliferação nuclear; Tratados internacionais; Organização intergovernamental; Política nuclear internacional; No proliferación nuclear -- Congresos; DIPLOMACIA; Tratados internacional; Organização intergovernamental; Política nuclear internacional; NUCLEAR NON-PROLIFERATION.; DISARMAMENT AGREEMENTS; TREATY REVIEW; CONFERENCES; TREATIES (TEXT); Conference papers and proceedings